Pengaruh Budaya Kerja Terhadap Kinerja Pegawai di Kantor Kementerian Agama Kabupaten Gunung Mas Provinsi Kalimantan Tengah - Mambang Mambang; Harmini Harmini (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
This research aims to determine the influence of work culture on the performance of employees in the Office of the Ministry of Religious Affairs of Gunung Mas Regency of Central Kalimantan, by applying hypothesis as follows: